Prevention of Falls from Heights in Construction Using an IoT System Based on Fuzzy Markup Language and JFML - Rey-Merchán, María del Carmen; López-Arquillos, Antonio; Soto-Hidalgo, José Manuel (IOAP-MPDI, 2022)
The main cause of fatal accidents in the construction sector are falls from height (FFH) and the inappropriate use of a harness is commonly associated with these fatalities. Traditional methods, such as onsite inspections, safety communication, or safety training, are not enough to mitigate accidents caused by FFH associated with a poor management in the use of a harness. Although some technological solutions for the automated monitoring of workers could improve safety conditions, their use is not frequent due to the particularities of construction sites: complexity, dynamic environments, outdoor workplaces, etc. Then, the integration of expert knowledge with technology is a key issue. Fuzzy logic systems (FLS) and Internet of Things (IoT) present many potential benefits, such as real-time decisions being made based on FLS and data from sensors. In the current research, the development and test of an IoT system integrated with the Java Fuzzy Markup Language Library for FLS, to support experts’ decision making in FFH, is proposed. The proposal was checked in four construction scenarios based on working conditions with different levels of risk of FFH and obtained promising results.
Keywords: Construcción; IoT; Fuzzy Markup Language; JFML; Fall from height; Monitoring; Safety; Construction